Presser – the forgotten story. (October 2016) - Kasinathan, John; Le, Joey; Barker, Anthony; Sharp, Gillian
Objective: Regina v Presser [1958] VR 45, is the most seminal case regarding fitness to plead for accused persons in Australia and New Zealand. It is not widely understood that Presser was a 14-year-old boy with intellectual disability. We aim to describe a clearer narrative regarding Edward John Presser. Method: Review of attainable newspaper reports framed within an historical context of fitness and relevant case law. Results: Presser's narrative is described in greater detail than previously understood by clinicians and lawyers. Ramifications for fitness assessment are discussed including doli incapax and human rights considerations. Conclusions: The Presser criteria are widely applied; however, the case involved a 14-year-old boy with intellectual disability. Greater awareness of Presser's narrative assists clinicians providing expert evidence regarding fitness to plead for adolescents and persons with intellectual disability.